Direct selective laser trabeculoplasty in open angle glaucoma study design: a multicentre, randomised, controlled, investigator-masked trial (GLAUrious). Issue 1 (25th August 2021) - Congdon, Nathan; Azuara-Blanco, Augusto; Solberg, Yoram; Traverso, Carlo E; Iester, Michele; Cutolo, Carlo Alberto; Bagnis, Alessandro; Aung, Tin; Fudemberg, Scott J; Lindstrom, Richard; Samuelson, Thomas; Singh, Kuldev; et al.
Abstract : Introduction: Laser trabeculoplasty is an effective and widely used treatment for glaucoma. A new laser technology, the Eagle direct selective laser trabeculoplasty (DSLT) device, may provide automated, fast, simple, safe and effective laser treatment for glaucoma in a broader range of clinical settings. This trial aims to test the hypothesis that translimbal DSLT is effective and not inferior to selective laser trabeculoplasty (SLT) in reducing intraocular pressure (IOP) in open angle glaucoma (OAG). Methods and analysis: This is a multicentre, randomised, controlled, investigator-masked study. The primary efficacy outcome is intergroup difference in mean change from baseline IOP measured at 6 months. Secondary outcomes include mean percentage reduction in IOP at 3, 6 and 12 months; proportion of participants with at least 20% reduction in IOP from baseline at 6 months; change in ocular hypotensive medications at 12 months and evaluation of safety. Participants were aged >= 40 years with OAG, including exfoliative or pigmentary glaucoma, or ocular hypertension with untreated or washed out IOP 22–35 mm Hg. Treatments: DSLT: 120 shots, 3 ns, 400 µm spot size, energy 1.4–1.8 mJ delivered at the limbus over 2 s. SLT: approximately 100 shots, 3 ns, 400 µm spot size administered 360 degrees at the limbus using any gonioscopy lens, energy 0.3–2.6 mJ. A sample size of 164 is sufficient to detect a non-inferiority margin of 1.95 mm Hg for change from baseline IOP. Clinical trial registration number: NCT03750201, ISRCTN14033075 .